2016
DOI: 10.1186/s13054-016-1518-8
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis 2016 Paris

Abstract: Background Despite advances in diagnostic methods and antibiotic therapy, community-acquired pneumonia (CAP) is still a major cause of morbidity and mortality worldwide. Risk of CAP has been attributed to pathogen virulence, host susceptibility and epidemiologic factors. A significant number of patients with CAP develop severe complications, such as sepsis, acute respiratory distress syndrome (ARDS), multiple organ dysfunction syndrome (MODS) and less fatal conditions (pleuritis, empyema) and syndromes (acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Then, the levels of AMM in patients were examined in the dynamics. It is shown that aromatic metabolites accurately relect the eiciency of ICU treatment and the prognostic signiicance of the some aromatic metabolites is higher than that of lactate [20].…”
Section: Sepsismentioning
confidence: 99%
“…Then, the levels of AMM in patients were examined in the dynamics. It is shown that aromatic metabolites accurately relect the eiciency of ICU treatment and the prognostic signiicance of the some aromatic metabolites is higher than that of lactate [20].…”
Section: Sepsismentioning
confidence: 99%